The scar effects of unemployment on electoral participation: withdrawal and mobilization across european societies - Azzollini, L (Oxford University Press, 2021)
Does unemployment increase or decrease electoral participation? A considerable body of work has examined this classic question, focusing on individual and contextual unemployment. However, this literature has scarcely examined the role of past experiences of unemployment, and not yet addressed their interaction with contextual unemployment. In this article, we extend the framework of unemployment scarring to study electoral behaviour. First, we posit that unemployment scars decrease electoral participation. Second, we formulate competing hypotheses on the macro-micro interactions between unemployment rates and scarring at the country, NUTS1 and 2 levels. We test these hypotheses relying on Rounds 4-8 (2008-2016) of the European Social Survey, for 26 countries. Results from logistic regressions with country and year fixed effects indicate that citizens with long unemployment scars are 9% less likely to vote than the non-scarred. We further find that higher unemployment rates at the sub-national levels slightly increase turnout, while there is no significant effect at the country level. For the sub-national levels, we find that lower unemployment rates exacerbate the individual scarring effect on turnout up to 13%. These findings remark that the framework of the scar effects of unemployment further illuminates the relationship between social stratification and political behaviour.